Разработка методов формирования представления сформулированного требования к информационной системе на уровне знаний - Евланов, М. В. (My University, 2015)
Розглянуто задачу розробки методів формування представлень функціональних вимог до інформаційної системи на рівні знань. Розроблені методи дозволяють створювати знання-орієнтовані моделі вимог до інформаційної системи. Ці моделі можуть служити базою для формування раціонального опису архітектури створюваної інформаційної системи. The problem of developing methods for the formation of functional requirements for the information system at the knowledge level is considered. The developed methods allow creating knowledge-oriented models of requirements to the information system. These models can serve as a basis for the formation of a rational description of the architecture of the information system being created.
Keywords: информационная система; функциональные требования; паттерны проектирования; фрейм; связь